Yellow ZnxNi1-xWO4 pigments obtained using a polymeric precursor method - de Oliveira, Andre Luiz M.; Ferreira, Jailson M.; Silva, Marcia R. S.; Braga, Glauco S.; Soledade, Luiz E. B.; Maurera Maria Aldeiza, M. A.; Paskocimas, Carlos A.; Lima, Severino J. G.; Longo, Elson [UNESP]; de Souza, Antonio Gouveia; Garcia dos Santos, Ieda M. (Elsevier B.V., 2008)
New tungstate-based ceramic pigments, displaying ZnxNi1-xWO4 stoichiometry, were obtained at low temperature using a polymeric precursor method. The powder precursors were milled in an attritor mill in an alcoholic rnedium and heat treated for 12 h. yielding homogeneous and crystalline powder pigments. Characterization (TG/DTA, XRD, IR and colorimetry) showed that mass loss increased with increasing Zn contents. Despite the presence of secondary phases and impurities, the wolframite phase was present in all samples. IR analysis revealed bands related to Me-O and [WO6](6-) group stretching was observed. The intensity of the yellow color of the pigments increased with increasing amount of nickel. (c) 2007 Elsevier Ltd. All fights reserved.
Keywords: wolframite; yellow pigments; tungstate; absorbance; colorimetry